SUBALTERNITAS TOKOH DIAH AYU DAN MAHARANI: ANTARA KUTUKAN DAN SENJATA - Irmawati Irmawati; Wahyu Gandi G (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
The story of “Kutukan Dapur” by Eka Kurniawan presents a colonial setting: Dutch colonialism and postcolonialism in the image of two characters, Diah Ayu and Maharani. Maharani is in patriarchal shackles, which is ingrained in her family life and social structure. Meanwhile, Diah Ayu is in the bonds of Dutch colonialism, which is brought back by the author. Both are in a subaltern position but in different conditions. Based on this description, this research asks two questions which are analyzed using Gayatri Spivak's subaltern theory, (1) what the position of Diah Ayu and Maharani in "Kutukan Dapur" short story, and (2) how the subaltern is constructed through the efforts of the two characters to get out of that position is. The method used is qualitative. The narratives are classified and analyzed to understand the subaltern's position and construction and its resistance efforts. This research indicates that Maharani and Diah Ayu are subalterns of Maharani dominated by patriarchy, while Diah Ayu is dominated by Dutch colonialism. Maharani fought back, but only with an idea or ideas. Unlike Diah Ayu, she is able to fight in a real form. However, as the author, Eka is trapped in a biased construction in addition to gender bias and representation. In subaltern studies, representation is only a tool towards more real domination. The two figures seem to be fighting against the power structure (colonial and patriarchal) but are still trapped in the dominance of the other.